Didaktične aplikacije fotografskih tehnik pri likovnovzgojnem delu in pedagoške metode za izvajanje likovnih tem brez fotokamere - Rijavec, Stanko (Revija za elementarno izobraževanje, 2009)
Didactic applications in photography for work in art education and pedagogical methods for teaching art themes without a camera. The article deals with some didactical methods connected with specific photographic methods and techniques. These techniques offer a lot of possibilities for creative expression based on point, line, shape and light-dark photography. The article puts stress on STAROGRAM - a technique that uses wax and KEMOGRAM - a technique based on manipulating photos with a developer and fixer. Certain artistic concepts, methods and chemical specifications are also discussed. The material needed for the didactical use of these techniques is specified.